Salmeterol's extreme b2 selectivity is due to residues in both extracellular loops and transmembrane domains - Baker, Jillian G.; Proudman, Richard G.W.; Hill, Stephen J. (American Society for Pharmacology and Experimental Therapeutics, 2015)
Salmeterol is a long-acting b2-agonist, widely used as an inhaled treatment of asthma and chronic obstructive pulmonary disease. It has very high b2-affinity (log KD 28.95) and is very selective for the b2-adrenoceptor (1000-fold selectivity over the b1-adrenoceptor). This study used a mutagenesis approach to determine the exact amino acids in the human b2-adrenoceptor responsible for this very high selectivity. Wild-type b2- and b1-adrenoceptors, chimeric b2/b1-adrenoceptors, and receptors with single-point mutations were transfected into Chinese hamster ovary-K1 cells, and affinity and function were studied using [3H]CGP 12177 [(2)-4-(3-tert-butylamino-2-hydroxypropoxy)- benzimidazol-2-one] whole-cell binding and [3H]cAMP accumulation. Extracellular loop 3 (and specifically amino acid K305) had the largest single effect by reducing salmeterol’s affinity for the b2-adrenoceptor by 31-fold. H296 in transmembrane 6 also had a major effect (18-fold reduction in salmeterol affinity). Combining these, in the double mutant b2-H296K-K305D, reduced salmeterol’s affinity by 275-fold, to within 4-fold of that of the b1-adrenoceptor, without affecting the affinity or selectivity of other b2-agonists (salbutamol, formoterol, fenoterol, clenbuterol, or adrenaline). Another important amino acid was Y308 in transmembrane 7, although this also affected the affinity and selectivity of other agonists. F194 in extracellular loop 2 and R304 in extracellular loop 3 also had minor effects. None of these mutations (including the double mutant b2-H296K-K305D) affected the efficacy or duration of action of salmeterol. This suggests that the high affinity and selectivity of salmeterol are due to specific amino acids within the receptor itself, but that the duration of action is at least in part due to other factors, for example lipophilicity.